A cross-sectional study to assess the perceptions and experiences of tuberculosis patients about directly observed treatment in an urban slum, in Mumbai, Maharashtra, India - Sawase, Gautam Bhagwan; Acharya, Shrikala; Shinde, R. R. (International Journal Of Community Medicine And Public Health, 2016)
Background: India accounts for one-fifth of the global incident cases of Tuberculosis. The country presently has the world’s largest directly observed treatment, short course (DOTS) programme that has shown impressive results. However, to sustain the high treatment adherence & cure rates, awareness among patients about regular and complete treatment and availability of accessible DOT services are vital, especially in urban slum areas. The objectives were (1) to study the socio- demographic profile of patients diagnosed at Urban Health Center; (2) to assess their knowledge and perceptions about TB treatment; (3) to ascertain the accessibility of DOT services and the problems faced at DOT center and; (4) to find willingness of patients for private practitioner as a ‘DOT provider’. Methods: The cross sectional study is being conducted among TB patients diagnosed & taking DOT treatment at Urban health center, located in Malvani slums in Mumbai. All the patients (65), willing to participate, over 3 months of duration are included. A semi-structured and pretested questionnaire is used to interview the patients after obtaining their consent. The data is analyzed using SPSS version 16. Results: 76.9% of the patients were in economically productive age group (15-45 year), disease distribution was found slightly higher in males. Among total patients 35.4% were house wives, 20% were unemployed & 9% were students. All patients were aware that they are suffering from TB. 92.5% of new patients were as 96% among re-treatment category were aware about duration of treatment. 33.84% patients faced poor accessibility to take DOT from the existing DOT center. 33.8% patients preferred to take DOT from private practitioners in their area. Conclusions: Almost 1/3 patients cited inconvenience in accessing DOT services due to their work hours, long distance and expressed willingness for community DOT providers including private practitioner. These patients, in the circumstances, may not pursue Directly Observed Treatment under supervision, resulting in poor treatment adherence and drug resistance.